Comic layout analysis: adaptation dynamic approach layout for history subject in Malaysian secondary school / Fasehah Abdullah - Abdullah, Fasehah (2018)
Textbook as a dominant part usage in the Malaysia education and the problems like as the layout’s arrangement in History textbook too packed with text, describing the topic in one or two pages and re-evaluation of the suitability of the textbook design layout towards the implementation of innovation and creativity.